Effects of Foliar Treatments of Salicylic Acid on Apple (Malus domestica L.) Against Freezing - Bengü Türkyılmaz Ünal; Oğuzhan Mentiş; Ethem Akyol (Turkish Journal of Agriculture: Food Science and Technology)
In our study we aim to increase frost resistance and improve the yield and quality of apple is important in Turkey and world economy. Phenological and morphological observations, physiological and biochemical analyzes were carried out in apple (Malus domestica L.) plants. It was studied to determine the effects of foliar Salicylic acid (0, 500 ppm/plant and 1000 ppm/plant) on adaptation of this plant when exposed to freezing stress, the quality and yield. Leaf photosynthetic pigment contents, total protein amount, proline amount, superoxide dismutase and peroxidase enzymatic activities were measured. The study planned by random experimental design and statistical analysis of data with SPSS program (LSD test) were made. It was determined that fruit and shoot numbers were increased in samples exposed to 500 ppm salicylic acid and while fruit weights were increased in samples exposed to 500 ppm and 1000 ppm salicylic acid compared to the control. Also, colour of plants were darkened. Chla, chlb, total chl, proline, superoxide dismutase and peroxidase amounts were increased significantly compared to the control group. Increases occured in the carotenoid and the protein amounts are not significant statistically. In the light of obtained data, foliar application of salicylic acid were found to reduce the effects of freezing stress and to increase the yield and quality of apple plants.